2019
DOI: 10.1007/s13337-019-00512-x
|View full text |Cite
|
Sign up to set email alerts
|

Sequence diversity studies of papaya ringspot virus isolates in South India reveal higher variability and recombination in the 5′-terminal gene sequences

Abstract: Papaya ringspot virus (PRSV) is one of the most devastating viruses which causes huge damage to papaya plantations across the globe. PRSV is a positive sense RNA virus encoding for a polyprotein that is processed into ten proteins. In this study for the first time we analyzed the variability for 15 PRSV isolates from a selected geographical region of a South Indian state Karnataka, which is under intensive papaya cultivation. Variability studies were done for two genes at the 5 0 end of the viral genome, namel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 29 publications
7
6
0
Order By: Relevance
“…The highest recombination was detected towards the 5'region of the PRSV genome particularly including the first 1020 nt. The potential regions prone to recombination are 5'UTR and P1, thus playing a major role in PRSV genome dynamics as this information strengthen some preliminary findings 26 , followed by HC-Pro gene 39 and consistent with other potyviruses 40 as well. We conclude that PRSV from India (Meghalaya) (MF356497) acts as a major parent in this recent outbreak of recombination.…”
Section: Discussionsupporting
confidence: 84%
“…The highest recombination was detected towards the 5'region of the PRSV genome particularly including the first 1020 nt. The potential regions prone to recombination are 5'UTR and P1, thus playing a major role in PRSV genome dynamics as this information strengthen some preliminary findings 26 , followed by HC-Pro gene 39 and consistent with other potyviruses 40 as well. We conclude that PRSV from India (Meghalaya) (MF356497) acts as a major parent in this recent outbreak of recombination.…”
Section: Discussionsupporting
confidence: 84%
“…This clade shares a most recent ancestor with isolates from the USA (Hawaii and Texas), Mexico and France (Fig 2), supporting findings from other studies where a correlation between sequence diversity and geographic area was not apparent (11). No recombination events were predicted for any of the Ecuadorean or other American isolates, whereas the majority of recombinants were detected in Asian isolates, supporting previous results that place Asia as the origin center of PRSV (13,15,35). the DAG motif, in the CP of most potyviruses was shown to be hypervariable (37).…”
Section: Discussionsupporting
confidence: 84%
“…Studies based on the coat protein (CP) suggested that PRSV originated from southern Asia, as higher diversity levels were found among Indian and other Asian isolates compared to sequences from the rest of the world (11)(12)(13)(14). Further analyses using complete genomes of isolates from different geographical regions showed that recombination events, especially at the 5' end, and P1 gene, have played a pivotal role in the diversification of PRSV, supporting previous findings on the origin of the virus (14,15).…”
Section: Introductionsupporting
confidence: 76%
“…Recombination complicates phylogenetic analyses because various genome regions in a single individual may have different evolutionary histories. Accordingly, constructing phylogenies using different sections of SCMV and other potyviral genomes produces conflicting trees 35,36 . Recombination may also impede virus detection because increased genomic variation may lead to false negative results with common techniques such as PCR and antibody ELISA 11,37 .…”
Section: Introductionmentioning
confidence: 99%